Agile and SEMAT- Perfect Partners. - JACOBSON, IVAR; SPENCE, IAN; PAN-WEI NG (Communications of the ACM, 2013)
The article discusses the agile movement, which is an initiative to improve the ways in which software is developed, and the Software Engineering Method and Theory (SEMAT) initiative, which is a novel way of looking at the domain of software engineering. The authors argue that when the two initiatives are combined, it empowers teams to be innovative, to experiment, and to improve the results they deliver. Topics include what SEMAT adds to the agile movement, the support that SEMAT provides in helping organizations become agile, the goal of the SEMAT initiative, and what the agile movement add to SEMAT.